2004
DOI: 10.1177/0899764004265432
|View full text |Cite
|
Sign up to set email alerts
|

Too Much of a “Good” Thing? Insular Neighborhood Associations, Nonreciprocal Civility, and the Promotion of Civic Health

Abstract: This article examines whether a high number of neighborhood associations within a community promotes or hinders civic health and offers two concepts for civil society scholarship: the insular civil society organization (CSO), which is primarily or solely committed to internal development and membership cultivation, and nonreciprocal civility, which captures the absence of relational ties between such CSOs. Based on the analysis of two urban neighborhoods in Baltimore, Maryland, the authors found that a high nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Neighborhood and social organizational context can also interact with spatial location to affect the likelihood of collaboration (Granovetter 1973, Hall 1999, Jaroff et al 2009. Sometimes, neighborhood associations are unlikely to collaborate with adjacent associations; the proliferation of community groups in Baltimore occurred as a result of competition for resources in lower income neighborhoods (Meyer and Hyde 2004). To add to the complexity of collaboration, researchers have found that some stewardship groups tend to focus on a single parcel or neighborhood, while other groups will span neighborhoods and operate at much larger scales (Connolly et al 2013(Connolly et al , 2014.…”
Section: Spatial Effectsmentioning
confidence: 99%
“…Neighborhood and social organizational context can also interact with spatial location to affect the likelihood of collaboration (Granovetter 1973, Hall 1999, Jaroff et al 2009. Sometimes, neighborhood associations are unlikely to collaborate with adjacent associations; the proliferation of community groups in Baltimore occurred as a result of competition for resources in lower income neighborhoods (Meyer and Hyde 2004). To add to the complexity of collaboration, researchers have found that some stewardship groups tend to focus on a single parcel or neighborhood, while other groups will span neighborhoods and operate at much larger scales (Connolly et al 2013(Connolly et al , 2014.…”
Section: Spatial Effectsmentioning
confidence: 99%
“…Despite these apparent positive externalities, vibrant community organizational life may pose problems for public organizations, proliferating the influence of private interests and encouraging organized dissent against policy initiatives that are in the broader public interest. For example, where competition for political influence between social groups is more acute, it may become more difficult to secure agreement on common goals (Meyer, 2004). Thus, while one might anticipate that community organizational life offers the potential for fruitful co-productive activity, it might also be the source of serious community tensions and conflicts, which add to the costs of service delivery.…”
Section: Social Capital and Public Service Performancementioning
confidence: 99%
“…The contribution of this paper is the argument that neoliberalism, as an order of reason, has progressively diminished the capacity of nonprofits to fulfill their missionto engage their publics, to empower and give voice, an assertion that has implications for representative government given their pivotal role in state-society relations. Nonprofit political capacity develops through sustained engagement with a public that generates meaning (Chambers and Kopstein 2001), mobilizes citizens (Kim, Jang, and Dicke 2017), and enables an organization to act with them by advocating their lived experience (Meyer and Hyde 2004). The ways in which neoliberalist logic has dissipated the political capacity of nonprofits has been documented in the international development literature (See Banks, Hulme, and Edwards 2015;Kamat 2004;Manji and O'Coill 2002) where the expressed purpose of nonprofits was often overtly intended to foster democracy working through the medium of civil society.…”
Section: Introductionmentioning
confidence: 99%